THE EFFECT OF RETURN ON ASSETS AND PRICE TO BOOK VALUE ON STOCK PRICES - Meilin Veronica (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2022)
This study aims to analyze the effect of return on assets and price to book value on the share price of PT Ciputra Tbk. The data used is secondary data obtained through the documentation process. The analytical method used is multiple linear regression analysis. The results prove that return on assets (X1) has no effect on stock prices (Y). Meanwhile, price to book value (X2) has a significant effect on stock prices (Y). This research is expected to help companies to increase stock prices through return on assets and price to book value ratio.